RAC3 Promotes Proliferation, Migration and Invasion via PYCR1/JAK/STAT Signaling in Bladder Cancer - Cheng, Chuanyu; Song, Dongkui; Wu, Yudong; Liu, Bingqian (Frontiers in Molecular Biosciences, 2020)
Background: Bladder cancer (BCa) represents one of the most common malignant cancers with high incidence and mortality rates globally. Dysregulation of gene expression has been shown to play critical roles in cancer progression. RAC3 is up-regulated to play an oncogenic role in several cancers; however, the underlying mechanism of RAC3 in BCa is yet to be elucidated. Therefore, this study aimed to investigate the function and mechanism of RAC3 in BCa. Methods: Bioinformatics analysis was employed to demonstrate the expression of RAC3 and PYCR1 in BCa tissues, as well as, its correlation with the overall survival rate of BCa patients. RT-qPCR was performed to detect and quantify the mRNA levels of RAC3 and PYCR1 in BCa cells and immortalized human bladder epithelial cells. MTT, colony formation and Transwell assays were employed to determine cell proliferation, migration, and invasion. Western blotting was performed to detect and quantity proteins expressed. Results: Bioinformatics analysis showed that RAC3 was up-regulated in BCa tissues when compared to normal tissues. Patients with up-regulated RAC3 expression had lower overall survival than patients with down-regulated RAC3 expression. The mRNA level of RAC3 was higher in BCa cells than in immortalized human bladder epithelial cell. RAC3 promoted cell proliferation, migration, and invasion by activating Janus kinases (JAKs) and signal transducers and activators of transcription (STATs) signaling. Notably, RAC3 up-regulated PYCR1, which is positively correlated with RAC3, and thus played an oncogenic role in BCa cells. Moreover, we demonstrated that RAC3 overexpression activated JAK/STAT signaling via PYCR1 axis. Conclusion: RAC3 promoted cell proliferation, migration, and invasion. This is likely due to its role in activating JAK/STAT signaling, which was mediated by PYCR1. This study provides a novel biomarker and target for diagnostic or therapeutic intervention for BCa.